SEPSIS AND MULTIPLE ORGAN DYSFUNCTION IN THE INFECTION CAUSED BY COVID-19: A CASE REPORT (CIPEEX, 2022)
SEPSIS IS A CONDITION IN WHICH THERE IS DYSFUNCTION OR EVEN ORGAN FAILURE AND IS PRESENT IN THE EVOLUTION OF THE MOST DIVERSE INFECTIONS. BESIDES, THE INFECTION BY COVID-19 WITH PROGRESSION TO SEPSIS IS A REALITY FOR CERTAIN PATIENTS, THEREFORE, THIS CLINICAL CASE ADDRESSES A SITUATION OF SEPSIS AND THE WAY IN WHICH THE CONDUCTS MUST BE TAKEN TO REVERT THE PICTURE OF MULTIPLE ORGAN DYSFUNCTION. THE MAIN OBJECTIVE OF THIS REPORT WAS TO PRESENT THE CASE OF A 44-YEAR-OLD MALE PATIENT WHO CONTRACTED COVID-19 AND EVOLVED INTO SEPTIC SHOCK, WITH A SECONDARY BACTERIAL INFECTION. THE PATIENT PRESENTED A VERY SERIOUS CONDITION RESULTING FROM THE INFECTIOUS CONDITION, WHICH WAS MARKED BY RESPIRATORY FAILURE LEADING TO SEVERE ACUTE RESPIRATORY DISTRESS SYNDROME (ARDS) WITH HEMODYNAMIC INSTABILITY. HE REMAINED HOSPITALIZED IN THE INTENSIVE CARE UNIT (ICU) FOR 20 DAYS AND SOME ACTIONS WERE TAKEN TO REVERSE THIS SITUATION. STILL, IT WAS NECESSARY TO APPLY CONTINUOUS HEMODIALYSIS THERAPY, GIVEN THE RENAL DECLINE PRESENTED BY THE PATIENT. AFTER STARTING MEDICATION AND ASSOCIATED TREATMENTS, IT WAS POSSIBLE TO REVERSE THE CONDITION OF THIS PATIENT WHO, AT THE END OF THE STORY, MANAGED TO RECOVER. WITH THE ANALYSIS OF THIS CASE AND A LITERATURE REVIEW, IT WAS UNDERSTOOD THAT THE CORRECT MANAGEMENT IN THESE TYPES OF SITUATIONS CAN CHANGE THE OUTCOME OF FATALITIES CAUSED BY SEPSIS. HOWEVER, IT WAS CLEAR THAT THERE IS NO CONSENSUS AND STANDARD TREATMENT FOR THE MANAGEMENT OF INFECTIONS THAT LEAD TO SHOCK AND MULTIPLE ORGAN FAILURE, THUS, IT IS NOTED THE IMPORTANCE OF CONTINUING SCIENTIFIC PRODUCTION THAT SHARE REPORTS AND EVIDENCE ON HOW TO DEAL WITH THESE SITUATIONS IN THE BEST POSSIBLE WAY.
Keywords: sepse; multiple organ dysfunction; sequential evaluation of organic bankruptcy